Peningkatan Kualitas Media Dakwah Melalui Pelatihan PDCA (Plan Do Check Act) - Eddy E; Ari Usman; Haida Dafitri (Jurnal TUNAS, 2020)
One of the determinants of the success of delivering a da'wah message is the use of appropriate and quality media. To produce quality media can be done by implementing the PDCA program (Plan, Do, Check, Act). PDCA is continuous improvement and is a continuous cycle. Implementation of the PDCA cycle in improving the quality of da'wah media consists of, The implementation of the plan, among others: determination of the title, elaboration of the material, preparation of equipment, determination of the angle and background of the video image and others. Execution, among others: video shooting, image editing, sound editing and announcer. Checking, among others: conducting a thorough evaluation, such as the material/content of propaganda that will be delivered, video images, editing results, pronunciation. Actions, among others: following up on the evaluation results, conducting continuous improvement and standardizing.